Measurement and modelling for harmonic dynamic characteristics of a liquid-filled isolator with a rubber element and high-viscosity silicone oil at low frequency. (June 2020) - Sun, Xiaojuan; Zhang, Cheng; Fu, Qidi; Zhang, Hong; Dong, Hongquan
Highlights: A liquid-filled isolator with novel mechanical coupling structure is characterized by a coupled parallel combination. Forced response experiments are implemented. Three models are developed to address the nonlinear dynamic behavior at low frequency. Amplitude-, frequency-dependent and asymmetric nonlinearities are all reflected. The suspended system with the proposed isolator can be designed to achieve desired dynamic performance. Abstract: Key dynamic characteristics of a novel liquid-filled isolator with an annular orifice are investigated at low frequency by using experimental and analytical methods, both within the context of a simplified suspended cab model. The isolator is proposed to be characterized by a coupled parallel combination of a rubber path and a liquid path, through which motions or forces are transmitted to a resonant receiver, commonly an earthmoving machinery cab. To appropriately examine isolator dynamic properties, experimental results are compared with those of the corresponding rubber isolator while dynamic excitations under frequency-sweep and fixed-frequency are applied, respectively. It is observed that the liquid-filled isolator provides more desired dynamic performance for resonance mitigation and vibration isolation. It is suggested that an amplitude-dependent, softening nonlinearity presented in the dynamic stiffness should mainly result from the viscoelastic behavior of the silicone oil and also relate closely to the coupling properties. Also, small jerks in the acceleration response involved with asymmetric damping characteristics are present by a shock excitation, while almost no asymmetric characteristics are revealed under harmonic excitations although the isolator internal construction is asymmetric. Two models are developed by using Navier-Stokes equations, incorporating fluid rheological behavior and compressibility. Simulated and measured force-displacement loops are compared to indicate the models' validity. Accordingly, a lumped model (Model 3) consisting of cubic elastic force and fractional-power damping force terms is proposed, yielding a better prediction. The studies in this paper suggest key design parameters and form an essential first step for design optimization.